Kondisi Kemasan dan Pemasaran Bahan Stone Gips (Gips Tipe III) di Jakarta (Juli 1996-1998) - Mia Damiyanti (Faculty of Dentistry, Universitas Indonesia, 2015)
Rapid development in dental material sciences rendered various dental plaster production and one of them mostly used is dental stone plaster. According to survey conducted in Jakarta in 1997-1998, there are at least seven kinds of them. They are oftenly sold without marking (such as lot numbers, date of manifacture, net weight, physical properties) as regulations in accordance with ADA or ISO. This condition can affect entirely the materials using. On the other hand the prices highly increased (>300%) in 1997-1998 has made consumers preferring to choose the materials economically, although there are various brands in the market. The dentist should be informed about the importance of the packaging marking, so that they prefer to choose the right materials.